Peningkatan Kemampuan Menghafal Huruf Abjad Melalui Pendekatan Konstruktivisme: Single Case Study di MI As-Salafiyah Pule Kandat Kediri - Majidatun Ahmala; Intan Dwi Cahya Ningrum (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Third-grade students at the elementary level should have sharpened their abilities in intensive reading. However, researchers found an interesting case here, where there were students who had not even been able to memorize Indonesian alphabetical letters in class in the third grade of MI AS-Salafiyah Pule Kandat Kediri. Therefore, the purpose of this study is to improve the ability of students to memorize Indonesian alphabetical letters with a constructivism approach so that students are expected to be able to memorize the letters well and follow their friends in optimizing intensive reading. This research uses a qualitative descriptive method. Data collection techniques used are observation, interviews, and document analysis. Researchers use purposive sampling technique with single case study. The results of this study indicate that after the mentoring process memorizing the alphabetical letters was carried out for three months, students have been able to memorize the letters that have a similar level of similarity, able to read a sentence in which there are patent letters, and students become more confident to read in the form of paragraphs.